Winter Dreamer - Gum, Dennie R. frey50 (Lexington, KY Createspace, 2010)
Telisa Thomas' life is perfect with a good job, friends and a great lover, so she thought. In a few short weeks she is to be married to the handsome Devin Young. Devin is the dream man that all women want, caring, funny, attentive, and all hers. Telisa is plagued with nightmares of a secret form long ago, one she wishes to forget forever. With the nightmares comes the man that she must avoid at all cost if she is to keep a hold on her new life. Kincaid Johnson is the bad boy back home and he can not rest with the thought of Telisa's heart and very soul being in so much pain. He has come to the limit of his own willpower and must find a way to silence her out cry of pain once and for all. With time ticking and a renewed vow of love on his mind, Kindcaid will stop at nothing to make things right between the love of his life and himself. He may be crushed for loving someone who is out of reach. Is Telisa ready to face fate? Is Kincaid ready to hear the secrets about his past? It all begins with a winter dream...
Keywords: Romance; Modern day romance; Dreams